The role of trust and social presence in social commerce purchase intention - Masoodul Hassan; Zeeshan Iqbal; Bakhtawar Khanum (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2018)
Social commerce is a new advancement of e-commerce that merges the commercial and social activities by deploying social technologies into e-commerce sites. Social commerce reintroduces e-commerce from the perspective of social media/ networks. This study was aimed to evaluate the individuals' intention towards social commerce in Pakistani context. The research model was examined in the light of positivist paradigm adapted questionnaire distributed among the people to yield data about the study constructs. The researchers employed PLS-SEM approach by using Smart PLS software to examine the hypothesized relationships. The findings suggest that social presence significantly influences the individuals' intention towards social commerce with the mediation of customers' experience. Furthermore, trust disposition, integrity of seller, competency of seller, and benevolence of seller positively shape the trust in marketplace. Moreover, trust in marketplace directly and significantly influences the individuals' electronic word-of-mouth and purchase intention towards social commerce. Theoretically, these findings contribute to a better understanding of the effect of social presence and trusting beliefs on individuals' electronic word-of-mouth and purchase intention towards social commerce. Finally, practical implications for nurturing thriving businesses in social commerce environment along with limitations and directions for future research have also been provided.
Keywords: 330; social commerce; social network sites (SNS); trust in marketplace; purchase intention; electronic word of mouth (eWOM); online shopping